The effect of practical cooling strategies on physiological response and cognitive function during simulated firefighting tasks in a smoke-diving room - Rasoul Hemmatjo; Majid Motamedzade; Mohsen Aliabadi; Omid Kalatpour; Maryam Farhadian (Tabriz University of Medical Sciences, 2017)
Background: Firefighters often perform multiple emergency tasks during firefighting and life-saving operations under unknown and unpredictable conditions in hot and hostile environments. Therefore, this study examined the effect of cooling strategies on attenuating physiological and cognitive function response during simulated firefighting activities in a smoke-diving room. Methods: Each firefighter engaged in four conditions: namely (1) no cooling device; control (NC), (2) cooling gel containing menthol (CG), (3) cool vest (CV), and (4) cooling gel and cool vest (CG+CV). Cooling effects were evaluated by heart rate (HR), temporal temperature (TT), reaction time (RT), and the correct response (CR). Results: In the four experimental conditions, physiological response increased, reaction time improved, and correct response decreased after the activity relative to baseline. HR and TT were significantly lower at the end of the firefighting activity in the CG+CV (147.47 ± 4.8_bpm; 37.88 ± 0.20_○C) and CV (147.53 ± 4.67_bpm; 37.90 ± 0.22_○C) compared with the CG (153.67 ± 4.82_bpm; 38.10 ± 0.22_○C) and NC (154.4 ± 4.91_bpm; 38.11 ± 0.23_○C) conditions. RT and CR were significantly higher at the end of the activity in the CG+CV and CV compared with the CG and NC conditions. Conclusion: It is concluded that strenuous firefighting tasks have a detrimental effect on firefighters' physiological responses and cognitive function. The findings also revealed that CV was more effective than the CG in attenuating physiological responses and cognitive function during firefighting operations. Furthermore, combining CV with CG provides no additional benefit. It is concluded that cooling the body by the use of CV offered physiological and psychological benefit for firefighters during simulated firefighting activities.